Good regulatory practices and co-operation in trade agreements A historical perspective and stocktaking - Kauffmann, Céline (OECD Publishing, 2021)
This paper presents a stocktaking of standalone chapters in trade agreements dedicated to good regulatory practices and international regulatory co-operation. While standalone regulatory policy chapters in trade agreements remain a new development, they signal countries' increasing interest in elevating the visibility and ambition of regulatory policy, in line with their commitments in the 2012 OECD Recommendation of the Council on Regulatory Policy and Governance and the 2005 APEC-OECD Integrated Checklist on Regulatory Reform. Still, the level of ambition of these chapters varies widely depending on the state of play of regulatory policy in trading partners. By comparing the main substantive and structural features of these chapters, this stocktaking aims to inform the development of similar chapters in future trade agreements
Keywords: Governance; Trade; Australia; Brazil; Brunei Darussalam; Canada; Chile; Colombia; Japan; Mexico; New Zealand; Peru; Singapore; United States; Viet Nam